Difference in tetrodotoxin content between two sympatric planocerid flatworms, Planocera multitentaculata and Planocera reticulata. (15th January 2020) - Itoi, Shiro; Tabuchi, Sora; Abe, Misato; Ueda, Hiroyuki; Oyama, Hikaru; Ogata, Ryuya; Okabe, Taiki; Kishiki, Ayano; Sugita, Haruo
Abstract: Planocerid flatworms and the related species (Platyhelminthes: polycladida) are known as tetrodotoxin (TTX)-bearing organisms, and they contribute to toxification of marine organisms at higher trophic levels, such as pufferfish and sea slugs. However, little is known of their biology or ecology. In this study, we therefore investigated the occurrence and toxicity of two sympatric planocerids, Planocera multitentaculata and Planocera reticulata, in intertidal zones of the central region of mainland Honshu, Japanese Islands. Planocera multitentaculata was much more abundant than P. reticulata . Body weight was greater in P. multitentaculata than in P. reticulata . Although a significant difference in TTX concentration was not observed between the two species, total TTX content per individual was greater in P. multitentaculata . Highlights: P. multitentaculata was much more abundant than P. reticulata . Body weight of P. multitentaculata was significantly greater than that of P. reticulata . TTX concentrations were >10 μg/g in almost all planocerids. TTX content in planocerids was related to body weight.